Analisis Penerapan Inovasi Administrasi Perpajakan Dalam Optimalisasi Penerimaan Pajak Di Era Revolusi 4.0 - Hannah Dwi Widyaninngsih; Notika Rahmi (Jurnal Ilmu Administrasi Publik, 2021)
Innovation in tax administration is a method to improve public welfare in any aspect, especially in tax income. The implementation, supervision, and control in tax collection can improve the involvement of taxpayers which currently is information technology - based. In the 4.0 industrial revolution era wh ich is all-technology, this is a new breakthrough to minimize deviation cases on tax income. The research questions are: how is the implementation of tax administration innovation in the optimization of tax income in the 4.0 industrial revolution era, what are the obstacles faced in the implementation of tax administration innovation in the optimization of tax income to improve taxpayer’s compliance in the 4.0 industrial revolution era, and what are the efforts to overcome the obstacles faced in the implementation of tax administration innovation in the optimization of tax income to improve taxpayer's compliance in the 4.0 industrial revolution era? This research was conducted using qualitative approach and descriptive method. The result of the research showed that the implementation of tax administration innovation in the optimization of tax income in the 4.0 industrial revolution era at the Regional Office of Directorate General of Tax in Central Jakarta had performed well; however, there were still problems such as system issue and hacker attack.